Extensive chemical and bioassay analysis of polycyclic aromatic compounds in a creosote-contaminated superfund soil following steam enhanced extraction. (1st November 2022) - Titaley, Ivan A.; Trine, Lisandra Santiago Delgado; Wang, Thanh; Duberg, Daniel; Davis, Eva L.; Engwall, Magnus; Massey Simonich, Staci L.; Larsson, Maria
Abstract: Polycyclic aromatic compounds (PACs) are organic compounds commonly found in contaminated soil. Previous studies have shown the removal of polycyclic aromatic hydrocarbons (PAHs) in creosote-contaminated soils during steam enhanced extraction (SEE). However, less is known about the removal of alkyl-PAHs and heterocyclic compounds, such as azaarenes, and oxygen- and sulfur-heterocyclic PACs (OPACs and PASHs, respectively). Further, the impact of SEE on the freely dissolved concentration of PACs in soil as well as the soil bioactivity pre- and post-SEE have yet to be addressed. To fulfil these research gaps, chemical and bioanalytical analysis of a creosote-contaminated soil, collected from a U.S. Superfund site, pre- and post-SEE were performed. The decrease of 64 PACs (5–100%) and increase in the concentrations of nine oxygenated-PAHs (OPAHs) (150%) during SEE, some of which are known to be toxic and can potentially contaminate ground water, were observed. The freely dissolved concentrations of PACs in soil were assessed using polyoxymethylene (POM) strips and the concentrations of 66 PACs decreased post-SEE (1–100%). Three in vitro reporter gene bioassays (DR-CALUX®, ERα-CALUX® and anti-AR CALUX®) were used to measure soil bioactivities pre- and post-SEE and all reporter gene bioassays measured soil bioactivity decreases post-SEE. Mass defect suspect screening tentatively identified 27 unique isomers of azaarenes and OPAC in the soil. As a remediation technique, SEE was found to remove alkyl-PAHs and heterocyclic PACs, reduce the concentrations of freely dissolved PACs, and decrease soil bioactivities. Graphical abstract: Image 1 Highlights: Steam enhanced extraction (SEE) removed alkyl-PAHs and heterocyclic-PACs in soil. Concentrations of freely dissolved 66 PACs decreased in post-SEE soil. In vitro reporter gene bioassays measured decreases in soil bioactivity post-SEE. Unexplained bio-TEQ activity were 74 (pre-SEE) and 54% (post-SEE). Mass defect suspect screening tentatively identified 27 isomers of heterocyclic PACs.